WATER FOOTPRINT GENERATED IN MILK PRODUCTION FROM A LIVESTOCK FARM. - Huera Ordoñez, Danny Stiven; Meneses Quelal, Washington Orlando (Tierra Infinita, 2023)
The present research was developed at 2950 meters above sea level in the north of Ecuador, Carchi province, Tulcán canton and had the objective of estimating the water footprint for milk production on the San Guillermo farm which has 150 hectares of which 48.76 hectares are dedicated to the production of pastures. To calculate the water footprint in milk, the blue, green and gray water footprint variables were determined by collecting information from the following data: yield of green forage (kg), percentage of dry matter (% DM), dry matter consumption (cms), milk production (l/cow/day), live weight of animals (kg), direct and indirect water consumption (l), water consumption in the stable (l) and consumption of water for washing milking equipment (l) among others. To calculate water consumption in forage production, the CROPWAT-FAO software was used through which the water requirement was estimated using climatological data of the soil and the crop. It was shown that to produce one liter of milk, 0.81 m3 of water is needed, of which 53 % is dammed due to the water requirement of the crop throughout its production cycle. The water footprint for each liter of milk produced on the farm was 805.7l liters, a value that agrees with literature research which shows that for each liter of milk around 1000 liters of water are needed.
Keywords: Agri-food; consumption; water footprint; dairy production